Information Systems A Manager's Guide to Harnessing Technology (Open textbook library., 2015)
Information Systems: A Manager's Guide to Harnessing Technology is intended for use in undergraduate and/or graduate courses in Management Information Systems and Information Technology. The teaching approach in Information Systems: A Manager's Guide to Harnessing Technology can change this. The text offers a proven approach that has garnered student praise, increased IS enrollment, and engaged students to think deeper and more practically about the space where business and technology meet. Every topic is related to specific business examples, so students gain an immediate appreciation of its importance. Rather than lead with technical topics, the book starts with strategic thinking, focusing on big-picture issues that have confounded experts but will engage students. And while chapters introduce concepts, cases on approachable, exciting firms across industries further challenge students to apply what they've learned, asking questions like: Why was Netflix able to repel Blockbuster and WalMart? How did Harrah's Casino's become twice as profitable as comparably-sized Caesar's, enabling the former to acquire the latter? How does Spain's fashion giant Zara, a firm that shuns the sort of offshore manufacturing used by every other popular clothing chain, offer cheap fashions that fly off the shelves, all while achieving growth rates and profit margins that put Gap to shame? Why do technology markets often evolve into winner-take-all or winner take-most scenarios? And how can managers compete when these dynamics are present? Why is Google more profitable than Disney? How much is Facebook really worth? The teaching approach in this text encourages students to think deeper and more practically about the space where business and technology meet. Every topic is related to specific business examples, so students gain an immediate appreciation of its importance. Rather than starting with technical topics, the book starts with strategic thinking, focusing on big-picture issues that interest students.